Cost and Quality Analysis: Why Quality Education Still Feels Expensive? - Kevin Zeni Wasono; R. Madhakomala; Linda Ika Mayasari (Eastasouth Institute, 2026)
Education is a crucial investment in human resource development, but in reality, quality education is still often considered expensive and remains inaccessible to many. This phenomenon raises questions about the relationship between cost and quality of education, as well as the factors that cause these high costs. This study aims to analyze the relationship between cost and quality of education and identify the causes of quality education remains financially burdensome. The method used is a descriptive qualitative approach through literature review of various scientific sources, policy reports, and relevant prior studies. The results of the study show that the high cost of education is influenced by various factors, including the increasing need for educational facilities, school operational costs, professionalism of educators, commercialization of education, and inequality in the distribution of government subsidies. In addition, it was found that high education costs are not always directly proportional to the quality of education, so efficient management and targeted policies are needed. The conclusion of this study emphasizes that the high cost of education is not solely caused by quality demands, but also by structural and policy factors that are suboptimal, necessitating collaborative efforts to improve access to education without sacrificing quality.Keywords: education costs, quality of education, access to education, inequality.